Juventude rural na agricultura familiar: diversidades de fluxos e resistências - Dambroski, Marilis (2024)
This dissertation results from research conducted in the settlement 08 de Junho, located in the municipality of Laranjeiras do Sul, in Paraná. The main objective of this study was to address the theme of rural youth in family farming, analyzing the diversity of flows between transitioning between rural and urban areas, migrating to the city, returning to rural areas, or staying in rural areas, as well as the resistance processes involved in these contexts. Much of the studies and debates on this topic focus on the migration of young people from rural areas to the city, raising concerns about the future of family farming and rural areas. To achieve the proposed objective, a methodological approach grounded in decolonial theory was adopted, which criticizes the universality of Eurocentric knowledge and questions the processes resulting from modernization, highlighting the forms of coloniality present in the fields of power, wisdom, being, and nature. The research involved the participation of fifteen young people from the settlement, eight males and seven females. A qualitative research methodology was used, including participant observation with field diary recording and semi-structured interviews, allowing for a more in-depth approach to the topic. It is essential to consider the geographical location of rural contexts, with some territories more distant from urban areas and others closer, as with the settlement in question, located just 8 km from the city. It is suggested that this fact may influence young farmers' socio-cultural and environmental relationships, enabling various experiences and flows. The data collected, and the information obtained from relevant observations to understand the dynamics of rural youth participating in the research were organized into categories reflecting the research objective. The analysis of this information revealed that the surveyed settlement presents a diversity of flows, with young people moving between rural and urban areas daily, some who have migrated to the city and returned, and those who divide their time between the city and the rural area throughout the week. Also, the analyses recognize the presence of coloniality in various aspects of these young people's lives. However, some resistances point to possible decolonial alternatives. Notably, despite this diversity of experiences, all the interviewed young people expressed the desire to remain in rural areas. From this, it is concluded that several elements make up the dynamics of the lives of these young people, such as access to land as a possibility for the family to stay in rural areas, whether through the struggle of grandparents and parents - MST, or the desire to have their land; family relationships and with the "environment"; the proximity of the settlement of 08 de Junho to the city, among others, which influences this choice, as it simultaneously maintains elements of the family farming way of life, while efficiently engaging with the urban and its opportunities (and difficulties), without the need for the youth of this settlement to migrate definitively to the city.